Penjadwalan Job Shop Mesin Majemuk Menggunakan Algoritma Non Delay Untuk Meminimumkan Mean Flow Time Dan Penentuan Due Date - Cahyanto, Wisnu Nur; , Hafidh Munawir, S.T., M.Eng (2016)
PT. Wangsa Jatra Lestari is a company engaged in the field of commercial printing, book binding, packaging, uv varnish, and laminating. The great variation in product, process flow pattern different - different, and use of the machine along with scheduling companies have constraints in the production process, namely the accumulation of intermediate goods and delays. Semi-finished goods inventory buildup due to the magnitude of the average flow time and the delay is due to the determination of the due date of the company that was not relevant to the actual conditions. The study was conducted to make a compound machine job shop scheduling algorithms using non delay. Algorithms non delay selected to minimize machine idle time so as to minimize the flow time of the average - average (mean flow time), total completion time (makespan), and to determine the due date. The study was conducted with problem identification, problem formulation, research purposes, restrictions on research, data collection, data processing, scheduling, determining the due date, the discussion and analysis, the last is the conclusion and suggestions. Scheduling algorithm using non delay generating total completion time of 30 822 minutes, average flow time - average of 6,031 minutes, and engine idle capacity of 21%. Algorithm non delay in completing the work more quickly than the methods the company with a difference of 6.522 minutes. Average - Average flow time non algorithm delay smaller than the methods the company with a difference of 2,911 minutes, that minimizes the semi-finished goods inventory. Scheduling non delay can reduce engine idle capacity by 8%. Methods of estimating the third company takes orders 9803 minutes (12 days) job 1, 4,471 minutes (5 days) job 2, and 4,235 minutes (5 days) job 3. Algorithm non membutuhan delay time of 17 045 minutes (20 days) job 1 , 11 714 minutes (14 days) job 2, and 11 466 minutes (14 days) 3 job.